Dual-Mode Integration of a Composite Nanoparticle in PES Membranes: Enhanced Performance and Photocatalytic Potential - Rund Abu-Zurayk; Nour Alnairat; Haneen Waleed; Aya Khalaf; Duaa Abu-Dalo; Ayat Bozeya; Razan Afaneh (Nanomaterials)
Polyethersulfone (PES) membranes are essential in separation processes; however, their inherent hydrophobicity can limit their effectiveness in water-intensive applications. This study aims to enhance PES membranes by modifying them with a NiFe2O4–nanoclay composite nanoparticle to improve both their hydrophilicity and photocatalytic potential as a photocatalytic membrane. The nanoparticles were synthesized using the sol–gel auto-combustion method and incorporated into PES membranes through mixed-matrix embedding (1 wt% and 3 wt%) and surface coating. X-ray diffraction confirmed the cubic spinel structure of the composite nanoparticles, which followed the second order kinetic reaction during the photodegradation–adsorption of crystal violet. The mixed-matrix membranes displayed a remarkable 170% increase in water flux and a 25% improvement in mechanical strength, accompanied by a slight decrease in contact angle at 1 wt% of nanoparticle loading. In contrast, the surface-coated membranes demonstrated a significant reduction in contact angle to 18°, indicating a highly hydrophilic surface and increased roughness. All membranes achieved high dye removal rates of 98–99%, but only the coated membrane system exhibited approximately 50% photocatalytic degradation, following mixed kinetics. These results highlight the critical importance of surface modification in advancing PES membranes, as it significantly reduces fouling and enhances water–material interaction qualities essential for future filtration and photocatalytic applications. Exploring hybrid strategies that combine both embedding and coating approaches may yield even greater synergies in membrane functionality.